2013
DOI: 10.1136/bmjopen-2013-004025
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of diabetic retinopathy with fibrates: a retrospective, matched cohort study

Abstract: ObjectivesTo compare the progression of diabetic retinopathy (DR) in people with type 2 diabetes treated with fibrates with that of non-exposed controls.DesignRetrospective, matched cohort study.SettingUK Clinical Practice Research Datalink (CPRD).Participants5038 people with type 2 diabetes with a history of fibrate exposure but without evidence of DR were identified. Three thousand one hundred and seventy-six (63%) people could be randomly matched to one non-exposed control; of these, 2599 (81.8%) were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…46 A subsequent retrospective evaluation similarly found a 22% reduction in diabetic retinopathy with fibrate treatment. 47 …”
mentioning
confidence: 99%
“…46 A subsequent retrospective evaluation similarly found a 22% reduction in diabetic retinopathy with fibrate treatment. 47 …”
mentioning
confidence: 99%
“…More recently, a large British retrospective cohort study compared the progression to diabetic retinopathy in patients with type 2 diabetes who were exposed or not exposed to fenofibrate. 51 The study included 5038 patients from 700 practices followed for five years and showed a reduction of diabetic retinopathy in those exposed to fibrates (33.4 v 40.4 events/1000 person years; P=0.002). Limitations were related to the retrospective design, but results supported a role for fenofibrate in primary prevention.…”
Section: Peroxisome Proliferator Activated Receptor α Agonist: Fenofimentioning
confidence: 99%
“…First, are these effects specific to fenofibrate or do they relate to fibrates more generally? Indeed, findings from a recent study in a real-world setting (n=5,038 type 2 diabetes patients) indicate that fibrate treatment (including bezafibrate, fenofibrate, ciprofibrate or gemfibrozil) was independently associated with reduction in progression to first retinopathy (primary outcome) [45]. Both bezafibrate (n=1739) and fenofibrate (n=1413) were the most commonly prescribed fibrates in this study (for a mean of 2.1 and 2.8 years, respectively).…”
Section: Reducing Residual Microvascular Riskmentioning
confidence: 94%